Leiomyosarcoma of the Thyroid Gland: A Review of the Literature and our Experience - Mevio Emilio; Mevio Niccolò; Cazzaniga Marco; Sbrocca Michele; Migliorini Luca; Mullace Mauro (Journal of Thyroid Cancer, 2015)
Primary thyroid leiomyosarcoma, is extremely rare, with only 19 cases reported in the literature to date. Onset of the tumor, which usually develops in only one lobe of the thyroid, is sudden and the tumor spreads rapidly to surrounding tissues. Preoperative differential diagnosis is extremely difficult. The long-term prognosis for the patient is extremely poor and unrelated to treatment. Indeed, thyroidectomy and neck dissection followed by adjuvant chemotherapy and/or radiation therapy have not been shown to affect rate of recurrence and long-term survival. The authors describe the case of a patient with leiomyosarcoma of the thyroid gland and review the relevant literature, considering the differential diagnoses and alternative treatment strategies.
Keywords: Leiomyosarcoma